Exploring entrepreneurial intention in Malaysia: A Bibliometric analysis of research trends from 2009 to 2024 - Wan Mustapha, Wan Masnieza; Baistaman, Julaina; Abu Bakar, Hatinah; Mat Nawi, Farahiyah Akmal (International Journal of Accounting, Finance and Business, 2025)
This study examines the research landscape on entrepreneurial intention in Malaysia from 2009 to 2024 through a bibliometric analysis of 148 academic publications indexed in the Scopus database. As Malaysia continues to establish itself as a significant player in entrepreneurship, understanding the factors influencing entrepreneurial intentions becomes essential for economic growth and job creation. The analysis reveals an increasing trend in publications from 2014, reflecting a growing interest in this area, with a notable peak in 2023. Most publications are in the form of academic articles, primarily contributed by leading institution like Universiti Teknologi MARA, Malaysia. Based on co-occurrence analysis using VOSviewer, the study identifies that much of the research is rooted in the Theory of Planned Behavior (TPB), emphasizing attitudes, perceived behavioral control, and subjective norms. Keywords such as "entrepreneurship education" and "self-efficacy" also indicate a strong focus on educational interventions to nurture entrepreneurial intentions. Despite the valuable insights gained, the study suggests expanding future research to explore social and cultural factors influencing entrepreneurial intention and include a more diverse demographic beyond university students. These findings serve as a resource for policymakers, educators, and researchers aiming to strengthen the entrepreneurial ecosystem in Malaysia.